The Influence of Ethical Leadership on Employee Well-Being: Mediating Knowledge Hiding and Moral Disengagement - Sari, Annisa; Suyono, Joko (IJHCM (International Journal of Human Capital Management), 2024)
This study examines the influence of ethical leadership on employee well-being by involving other antecedents as mediators and moderators. Knowledge hiding and moral disengagement act as mediators while self-enhancement and job involvement act as moderators. This quantitative research uses survey research conducted on three local government agencies. In this study, data were collected using a cross-section design with the help of questionnaires using a Likert scale. The data was analyzed using PLS-SEM and processed with the help of Smart-PLS. The sampling technique uses non-probability sampling with convenience sampling method.